Revolutionising Marketing: Leveraging Blockchain and AI for Impactful Management - Sadat Karim; Shilpi saxena; Duja Alka Singh; Pankaj Deshmukh; Aditya Bibhishan Lokare; Omsingh Gopalsingh Gour; Arif Mohammad Sattar; Ranjan, Mritunjay Kr. (E-COMMERCE FOR FUTURE & TRENDS, 2023)
In today's rapidly evolving business landscape, marketing management faces numerous challenges, including effective decision-making, customer engagement, and data security. Advanced technologies like AI and Blockchain have revolutionized the marketing domain, providing novel solutions to address these challenges. AI plays an essential role in marketing management through its utilization of data analysis, predictive modelling, and automation, providing marketers with the ability to extract valuable insights from extensive data sources, facilitating data-informed decision-making. Furthermore, AI-driven chatbots and virtual assistants enhance customer interactions, making them more efficient and tailored, ultimately enhancing customer engagement and contentment. The combination of AI and marketing automation enhances operational efficiency, streamlines workflows, and enables real-time monitoring and optimization of marketing campaigns. Utilizing blockchain technology in marketing management establishes a decentralized and transparent platform that guarantees data integrity, security, and fosters trust among all parties involved. Through the implementation of blockchain, marketers can safeguard customer data, mitigate the risk of data breaches, and cultivate confidence among their clientele. Blockchain-enabled smart contracts facilitate secure and automated execution of marketing agreements, eliminating intermediaries and reducing transaction costs. Blockchain-based loyalty programs enable seamless and secure reward distribution, enhancing customer loyalty and retention. However, the integration of AI and Blockchain technology presents significant opportunities for businesses to gain a competitive edge in the digital era. By leveraging AI's data analytics and automation capabilities and Blockchain's data integrity and security features, organizations can make informed decisions, personalize marketing campaigns, build customer trust, and enhance operational efficiency. Future research should focus on addressing ethical concerns and technical challenges to maximize the benefits of AI and Blockchain in marketing management.